The Impact of Video Content #LifeAtShopee Towards Intention to Aply on SBM ITB Final Year Student (Journal of Business and Management, 2022)
The rapid growth and development of the e-commerce industry in Indonesia makes e-commerce need to maintain and continue to improve the quality of its services by having qualified human resources to have a high chance of outperforming their competitors. Unfortunately, the limited human resources in the Indonesian market have led to a talent war, especially for the digital industry including e-commerce. Therefore, Shopee as the number one e-commerce company in Indonesia needs to attract the best talent in the market through employer branding programs. One of the media that can be used is social media. One of Shopee's employer branding programs on social media is #LifeAtShopee. Unfortunately, #LifeAtShopee can be used by anyone, including external parties on extensive social media, so further analysis is needed to find out whether unofficial #LifeAtShopee has an influence on employer branding attractiveness and changes the desire of target talent to apply or not. This study aims to know the difference between employer attractiveness and intention to apply before and after talents watch the unofficial #LifeAtShopee content. Data were collected through online questionnaires to SBM ITB final-year students as key target talents of Shopee, then analyzed using Paired Sample T-Test to determine whether there is a difference in the average of the one group pre-test and post-test. The results show that watching #LifeAtShopee content has a significant effect on employer attractiveness and intention to apply.Keywords: Social Media Content, Employer Branding, Employer Attractiveness, Intention to Apply